2021
DOI: 10.3389/fimmu.2021.640190
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing Immunity to Japanese Encephalitis Virus Alters CD4 T Cell Responses to Zika Virus Inactivated Vaccine

Abstract: The epidemic spread of Zika virus (ZIKV), associated with devastating neurologic syndromes, has driven the development of multiple ZIKV vaccines candidates. An effective vaccine should induce ZIKV-specific T cell responses, which are shown to improve the establishment of humoral immunity and contribute to viral clearance. Here we investigated how previous immunization against Japanese encephalitis virus (JEV) and yellow fever virus (YFV) influences T cell responses elicited by a Zika purified-inactivated virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…(3) Study in humans In a phase 1 clinical trial of a ZIKV vaccine, participants preimmunized with the JEV vaccine maintained more durable ZIKV-specific CD4 + T cell responses, with more obviousness in conserved epitopes among flaviviruses, suggesting that prior JEV immunity altered the immunogenicity of subsequent ZIKV vaccine [46].…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…(3) Study in humans In a phase 1 clinical trial of a ZIKV vaccine, participants preimmunized with the JEV vaccine maintained more durable ZIKV-specific CD4 + T cell responses, with more obviousness in conserved epitopes among flaviviruses, suggesting that prior JEV immunity altered the immunogenicity of subsequent ZIKV vaccine [46].…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…Our current knowledge of cross-immunity to ZIKV is mainly derived from infection of DENV 9 or other aviviruses such as WNV 25 and YFV 26 , and were limited to investigating the interrelationships of two avivirus serocomplexes 27 . Although a few studies investigated the interplay of avivirus immunity in the context of JEV, which is endemic in SEAsia, these studies focused on animal immunization or ex vivo stimulation using PBMCs from JEV-experienced donors 28,29 . Here, we purport key insights for developing broadly neutralizing antibodies against aviviruses using various approaches, including serological or epidemiological information, huMAbs isolation with structure-guided epitope mapping and murine vaccination model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar experiments in mice using recombinant vaccinia virus that carried the genes for the E and NS1 proteins of MVEV showed complete protection with a subsequent challenge with MVEV by eliciting generation of neutralizing antibodies, rather than a CD8+ immune response when E protein was used; passive transfer of MVEV-infected human sera also conferred protection with a subsequent MVEV challenge [ 204 ]. Cross-protection due to neutralizing antibodies resulting from CD4 T cell expansion following infection after JEV immunization, but not with YF immunization, has also been reported against ZIKV and DENV [ 205 , 206 , 207 ]. Li et al reported cross-protection against all four serotypes of DENV following JEV immunization, using more than one JEV vaccine [ 208 ].…”
Section: Je Serocomplex Flavivirus Immune Responsementioning
confidence: 99%